Discovery of new populations and DNA barcoding of the Arapahoe snowfly Arsapnia arapahoe (Plecoptera: Capniidae) - Heinold, Brian D.; Gill, Brian A.; Belcher, Thomas P.; Verdone, Chris J. (Zootaxa, 2014)
The Arapahoe Snowfly, Arsapnia arapahoe (Nelson & Kondratieff)was recently discovered in six different first-order streams outside of the Cache la Poudre River Basin where it was previously considered endemic. Specimens of A. arapahoe were always collected in much lower relative abundance, 1.09% (±2.3SD), than other sympatric adult capniids. The first mitochondrial deoxyribonucleic acid (DNA) barcodes for A. arapahoe and A. coyote (Nelson & Baumann) are presented and compared with those of A. decepta. DNA barcoding was not able to differentiate between A. arapahoe and A. decepta Banks but it was able to indicate that A. coyote is specifically distinct.